O ensino de Língua Portuguesa: os documentos oficiais e a construção do discurso pedagógico do professor da rede Estadual de Ensino de Carapicuíba - Ruotti, William (2016)
In this thesis, part of the line of research Reading, Writing and English Language Teaching, the Program of Postgraduate Studies in Portuguese at PUC-SP, I investigate the relations between the SEE-SP and its institutional discourse and the potential impacts on acting teacher of Portuguese who teaches in the public schools of the city of Carapicuíba. The objective of the research is to identify and discuss the power structure established by SEE-SP, through its official documents, in the constitution of pedagogical discourse around the performance of this teacher. Thus, I develop this study in the light of Critical Discourse Analysis (CDA), the side proposed by Fairclough (2003, 2008, 2010) and Critical Realism (RC), from what has Resende and Ramalho (2009) and Bhaskar (1998). The analysis focused on documents that are part of the teacher as a career: the portarias do INEP / MEC that determine the evaluation of ENADE and what is expected of the future teacher, graduated in Letters; the clippings of notices to join the state system of São Paulo teaching by drawing a comparison between the 1998 contests, in 2003, 2010 and 2014, 1996 LDB post in which establish the profile and knowledge necessary for the teacher formed and ticket seeker ; Currículo do Estado de São Paulo de Língua Portuguesa, the Matrizes de Referência para a Avaliação SARESP, guidance on the AAP and, finally, the Diretrizes Norteadoras da política Educacional do Estado de São Paulo - 2015-2018, the actions of regulators teacher in the classroom. Think of these moments in the construction of pedagogic discourse of the teacher is very important considering that in this process, particular and individual, the teacher confronts what is put by the Secretariat and the experiences that brings with it, basing their way of being, of representing and acting in the world. The results showed us the need for reflection on the institutional texts on education make increasingly part of the discussions held by the Portuguese Language teachers at different times of training, in order to elucidate and clarify a simple mechanical causality that the teaching process and learning can become